Topoanálise do romance O Mundo de Flora, de Angela Gutiérrez, à luz de Gaston Bachelard - Dutra, Nádya Brito Gurgel Correia (2023)
This thesis analyzes the novel “O Mundo de Flora”, by Angela Gutiérrez, published in 1990, under the perspective of the topoanalysis of the French phenomenologist Gaston Bachelard. To do this, we will take his work “A Poética do Espaço”, published in 1958. The topoanalysis revisited by Ozíris Borges will also be studied, as well as the novel literary geography, focusing on the studies of Tiago Cavalcante. We will also analyze Gutiérrez’s literary stylistics under the precepts of Nilce Sant’anna Martins and Vicente Martins. The motivation or basic issue is to praise Gutierre's work, taken by the avant-garde narrative style and presenting the city of Fortaleza from the end of the 19th century until the 1980s, providing us with a journey to a space of mansions, trams, a profusion of trees, libraries in homes, clothing and furniture from times gone by. The analysis categories to be applied are based on the aforementioned phenomenological theory, aiming to study the space that the protagonist, Flora Fernández, presents to us, prioritizing two neighborhoods, Downtown and Mondubim, as well as based on the analysis categories of geography and literary stylistics, extremely steeped in Ceará. In general terms, for methodological purposes, we will use the reading of the Angelian novel that founded this research and the other works in the aforementioned categories through a vertical and investigative assessment of its themes and styles, aiming to strengthen studies on Ceará Literature and about Angela Gutiérrez.